PEMBERDAYAAN MASYARAKAT UMKM USAHA LENTO DI DESA DRANCANG KABUPATEN GRESIK - Abdillah, Khubbi; Fitryani, Fitryani; Nagayomi, Tamara Mutiara; Alfirdaus, Resta Rahma (STIE Pelita Nusantara, 2023)
Community empowerment activities were carried out in Drancang Village, Menganti District, Gresik Regency through real work lectures (KKN). The aim of this service is to provide training about digital marketing to residents and assistance in packaging food products to Lento Micro, Small, and Medium Enterprises (MSMEs). The method used in implementing this service is giving direct lectures to residents and providing assistance to MSMEs business locations about improving product quality by packaging food products more attractively and hygienically. The result of this service activity is that residents increasingly understand the concept of digital marketing and are starting to be inspired to become entrepreneurs by utilizing online business. For MSMEs actors, Lento’s business is expected to produce quality food products with attractive packaging and hygiene is maintained.